A GPU approach to fortran legacy systems - Méndez, Mariano (2012)
A large number of Fortran legacy programs are still running in production environments, and most of these applications are running sequentially. Multi- and Many- core architectures are established as (almost) the only processing hardware available, and new programming techniques that take advantage of these architectures are necessary. In this report, we will explore the impact of applying some of these techniques into legacy Fortran source code. Furthermore, we have measured the impact in the program performance introduced by each technique. The OpenACC standard has resulted in one of the most interesting techniques to be used on Fortran Legacy source code that brings speed up while requiring minimum source code changes.